Idealized Single-Forcing Gcm Simulations With Ncar Cesm - Erb, Michael; Jackson, Charles; DiNezio, Pedro (Zenodo, 2018)
This repository contains a set of single-forcing general circulation model (GCM) simulations run with the National Center for Atmospheric Research (NCAR) Community Earth System Model version 1.2 (CESM1.2). In each of these equilibrium simulations, one climate forcing was altered while all others were held constant at preindustrial levels, modeling the climate response to individual climate forcings. Simulations were run for obliquity (low and high obliquity), precession (four phases of the precession cycle with high eccentricity, and one simulation with eccentricity set to zero), half CO 2 , and LGM-sized ice sheets. The values chosen for the orbital simulations represent the extreme values of the past 900 thousand years. Simulations were run for at least 500 years, and forcings do not change from year to year. The uploaded files are 100 year (or longer) monthly climatologies. For most simulations, variables are presented for the atmosphere (atm), sea ice (cice), land (clm2), and river runoff (rtm). For the ice sheets simulation and its corresponding preindustrial simulation (0ka), only atmospheric output is presented; to inquire about other fields for those simulations, please contact Pedro DiNezio at pdn@ig.utexas.edu. Ocean files are not currently available; please contact Michael Erb at michael.p.erb@gmail.com if you are interested in those results. === FORCINGS === Preindustrial climate forcings for the 0ka_0urb simulation were set to the following values: - Obliquity: 23.44107° - Longitude of perihelion: 102.7242° - Eccentricity: 0.01670772 - CO 2 : 284.7 ppm - Ice sheets: 0 ka BP The remaining simulations explore the climate response to a change in one of these forcings, with all other forcings set to preindustrial levels. Forcings are specified as follows: - lo_obliq and hi_obliq: Obliquity is set to 22.079° or 24.480°, respectively. - 0_AEQ, 90_WSOL, 180_VEQ, and 270_SSOL: Perihelion occurs at the NH autumnal equinox, winter solstice, vernal equinox, or summer solstice, respectively, with eccentricity set to 0.0493. This corresponds to a longitude of perihelion of 0°, 90°, 180°, or 270°, respectively. - ECC_0: Eccentricity is set to 0. - half_CO2: CO 2 is set to 142.35 ppm. - 21kaGlac: Ice sheets and sea level are set to Last Glacial Maximum (LGM) levels. Ice sheets come from the Paleoclimate Modelling Intercomparison Project Phase III (PMIP3) reconstruction, with ice shelves added in the western Labrador Sea. A note about preindustrial simulations: Some details of the model setup differ between the ice sheet simulation and the other simulations. Because of this, if a preindustrial control simulation is wanted for analysis, it is recommended that you use certain preindustrial simulations for certain comparisons, as follows: - 0ka_0urb (BG1850C5CN): Control simulation for all simulations except ice sheets. - 0ka (B1850C5): Control simulation for ice sheets (21kaGlac) simulation. === NOTES === More detailed description of these simulations, as well as results, can be found in the following papers: Erb, M. P., C. S. Jackson, A. J. Broccoli, D. W. Lea, P. J. Valdes, M. Crucifix, and P. N. DiNezio, in press: Model evidence for a seasonal bias in Antarctic ice cores. Nature Communications. Bosmans, J. H. C., M. P. Erb, A. M. Dolan, S. S. Drijfhout, E. Tuenter, F. J. Hilgen, D. Edge, J. O. Pope, and L. J. Lourens, in press: Response of the Asian summer monsoons to idealized precession and obliquity forcing in a set of GCMs. Quat. Sci. Rev. Bhattacharya, T., J. E. Tierney, and P. DiNezio, 2017: Glacial reduction of the North American Monsoon via surface cooling and atmospheric ventilation. Geophys. Res. Lett. , 44 , 5113-5122, doi:10.1002/2017GL073632. DiNezio, P. N., J. E. Tierney, B. L. Otto-Bliesner, A. Timmermann, T. Bhattacharya, N. Rosenbloom, and E. Brady, in review: Glacial changes in tropical climate amplified by the Indian Ocean. Note that the monthly data analyzed in these papers is sometimes converted to a common fixed-angular calendar in which every "month" corresponds to a 30° arc of Earth's orbit. This was done because changes in precession affect the speed at which Earth travels through different parts of its orbit according to Kepler's second law, complicating the comparison of months in different precession experiments. However, the results provided in this repository use the model's original fixed-day calendar. Computing resources (ark:/85065/d7wd3xhc) were provided by the Climate Simulation Laboratory at NCAR's Computational and Information Systems Laboratory, sponsored by the National Science Foundation and other agencies. If you use these simulations for research, please let the authors know. For a similar set of experiments using another model (GFDL CM2.1), see doi:10.5281/zenodo.1194480. Contact: Michael Erb Postdoctoral Scholar at Northern Arizona University michael.p.erb@gmail.com : Support for these simulations was provided in part by the University of Texas Institute for Geophysics (UTIG). The ice sheets simulation (21kaGlac) and corresponding preindustrial simulation were supported by National Science Foundation (NSF) grants AGS-1204011 and OCN-1304910.